Rare Case of Buccal Exostosis in Edentulous Mandibular Body Region - Rani, Amita; Poswal, Rajni (Journal of Orofacial Research, 2015)
Buccal exostoses are benign, broad-based surface masses of the facial aspect of the maxilla and less commonly, the mandible. It is believed that this is one way, bone responds to stresses applied to it. They begin to develop in the early adulthood and may slowly enlarge over the years. To the best of our knowledge, it is the second reported case of single buccal exostosis in mandibular molar region and first of its kind in edentulous mandible. The following paper presents a very rare and unique case of buccal-sided mandibular molar exostosis in an edentulous mandible of an old female and its surgical management.